Evaluation the Groundwater Regime under the Influence of Irrigation Water Leakage in the 7th Sector of the Lower Euphrates Basin – Syria - حايك شريف; يزبك ابراهيم (Latakia University Journal -Engineering Sciences Series, 2021)
Sector 7 is located on the right bank of the Euphrates River at the town of Albu Kamal on the Syrian-Iraqi border. Water from irrigation and irrigation canals are feed-in sources of free water in irrigated areas. Natural conditions must be preserved or artificial conditions suitable for plant growth. The research aims to evaluate the groundwater system in the studied sector, by studying changes in groundwater depths at the beginning, middle and end of the irrigation period, to determine the response of groundwater depths to irrigation water leakage, and then to estimate the amount of water leaking from it, and the speed of its leakage. Changes in groundwater depths are compatible in the loams and sandy gravel layers. However, these changes are sometimes disrupted by the differences of permeability between the two layers. There is a correlation between soil leaching values without a water compressor and the physical characteristics of the soil, such as texture, construction, soil integration and the extent to which the earth is serviced and invested. The research recommends the need to establish an appropriate drainage system that allows for the reduction of the ground water level, and to conduct deep soil erosion to disturb the soil and improve its permeability.